Applying Daoist Thoughts of Interconnectedness to Disaster Communities: Through the Lenses of Diaspora and Pluralism - Kim, Dugsam (Religions, 2024)
The human community confronts a plethora of disasters, including man-made epidemics like COVID-19, environmental problems such as water and food resource depletion, biochemical warfare, and even threats from human-created artificial intelligence. Consequently, it is appropriate to term our current community a “disaster community”. This paper delves into the issue of diaspora, intrinsically linked to the fragmentation problem in the disaster community, where each subgroup tends to focus solely on its own community. This issue is scrutinized by categorizing the diaspora into larger and smaller categories, with cases from both the international and domestic levels examined respectively within each category. Among the many Daoist philosophical concepts, this paper focuses on the Daoist principle of interconnectedness. In examining Daoist thought on interconnectedness, it also confirms that the notion of interconnectedness is being increasingly emphasized in modern society and across various academic disciplines. This perspective affirms the pluralistic nature of existence, while also underscoring the fundamental interconnectedness that underpins the myriad forms and phenomena. It provides a framework for addressing the challenges faced by the disaster community, particularly in relation to issues of diaspora, by emphasizing the need for coexistence and collective responsibility within a web of mutual relations. The philosophy innovatively applied from Daoism emphasizes “recognizing diversity based on Dao, while acknowledging that each existence is interconnected”. Here, “recognition of diversity based on Dao” underpins pluralism, and “interconnectedness of all existence” forms the fundamental solution to the diaspora problem. This approach could be extended as a strategic response to various disasters that the human community encounters. Therefore, this paper assesses the current state of the disaster community, the severity of the diaspora issue, and some cases both between and within nations. It also discusses the core of Daoist philosophy and its creative application to overcome these challenges. The disaster community should transition towards a sustainable and open community, and on this journey, by acknowledging our interconnectedness, we can find solutions to not only the disasters we confront but also to the diaspora problem.